IMMUNOPHENOTYPIC AND CYTOGENETIC FEATURES OF ACUTE LEUKEMIA IN CHILDREN OF THE ARKHANGELSK REGION: A RETROSPECTIVE STUDYN: A RETROSPECTIVE STUDY - A. S. Ulanova (Sibirskij Onkologičeskij Žurnal, 2021)
Background. For the proper diagnosis and optimal prognosis of acute leukemia (AL), a complex of clinical and laboratory methods is used. Among them, chromosomal analysis plays an important role. Cytogenetic markers of leukemic cells are widely used in clinical settings. WHO classification of Tumors of Haematopoietic and Lymphoid Tissues is based on a combined analysis of clinical, cytomorphological, immunophenotypic and cytogenetic findings. Immunophenotyping of blast cells using monoclonal antibodies has significantly improved the diagnosis of leukemia by detecting the grade of tumor differentiation. Aim: based on the results of immunophenotypic and cytogenetic examinations, to describe the structure of AL and to study the effect of cytogenetic abnormalities on the prognosis of acute leukemia in the child population of the Arkhangelsk region.Material and Methods. Archived data were used to analyze the results of cytogenetic and immunophenotypic examinations of all children aged 0–17 years in the Arkhangelsk region, who were diagnosed with AL in the period from January, 2004 to december, 2018. Results. Immunophenotypic examination of bone marrow blast cells in patients with AL revealed that B-linear lymphoblastic leukemia was the most common (74.8 %). Among the quantitative anomalies, hyperploidy was the most common (additional chromosomes 4, 10 and 17 were observed). The t(12; 21) was the most frequent structural chromosomal abnormality. The  philadelphia chromosome (ph) (9;22) was found in 6.5 % of cases. The highest risk of death was observed in AL patients with the acute myeloid leukemia phenotype (p<0.001). The overall survival in AL patients  significantly improved over the study period (p<0.001). Conclusion. No specific differences in the structure of chromosomal abnormalities were detected. All chromosomal abnormalities which usually have negative effects on the prognosis of the disease also showed negative impacts on the prognosis. Survival of AL patients significantly increased over the study period. The lowest survival was in patients with the acute myeloid leukemia phenotype.